Domestic violence, obesity and malnutrition in elderly people in a capital in southern Brazil - EpiFloripa Idoso Study - Araújo, Carolina Abreu Henn de; Warmling, Deise; Araújo, Pierre Guedes; Coelho, Elza Berger Salema (Ciência & saude coletiva, 2024)
Abstract The objective of this article was to verify the association between domestic violence and obesity and malnutrition in elderly people in Florianópolis, Santa Catarina, Brazil. Cross-sectional study evaluated in the EpiFloripa Elderly cohort in 2013/2014. The outcomes were body mass index (BMI) and abdominal obesity (increased WC). Violence against elderly people was measured using the HawlekSengstock Elder Abuse Screening Test (H-S/EAST) instrument, and IPV using the Conflict Tatics Scales Form R (CTS-1) instrument. Logistic regression and multinomial logistic regression models were used. It was observed that men had a greater chance of abdominal obesity when in situations of violence and in the potential abuse dimension. Women were more likely to have abdominal obesity in the dimension of violation of personal rights or abuse, when they suffered IPV and when they were perpetrators of IPV. In relation to BMI, elderly women in situations of violence were associated with a greater chance of being overweight and those who suffered IPV. On the other hand, men in vulnerable situations were more likely to be underweight. It is concluded that violence against elderly people and IPV generate an asymmetric impact on nutritional status in relation to sex. Resumo O objetivo deste artigo foi verificar a associação entre a violência doméstica com a obesidade e a desnutrição em pessoas idosas de Florianópolis, Santa Catarina, Brasil. Estudo transversal avaliados na coorte EpiFloripa Idoso em 2013/2014. Os desfechos foram o índice de massa corporal (IMC) e a obesidade abdominal (CC aumentada). A violência contra pessoa idosa foi mensurada através do instrumento HawlekSengstock Elder Abuse Screening Test (H-S/EAST), e a VPI por meio do instrumento Conflict Tatics Scales Form R (CTS-1). Utilizou-se modelos de regressão logística e regressão logística multinomial. Observou-se que os homens apresentaram maior chance de obesidade abdominal quando em situação de violência. Já as mulheres apresentaram maior chance de obesidade abdominal em situação de abuso direto quando sofreram violência por parceiro íntimo (VPI) e quando foram perpetradoras desta violência. Em relação ao IMC, as mulheres idosas em situação de violência e que sofreram VPI foram associadas às maiores chances de sobrepeso. Em contrapartida, os homens em situação de vulnerabilidade demonstraram maior chance de baixo peso. Conclui-se que a violência contra pessoa idosa e a VPI geram impacto assimétrico sobre o estado nutricional em relação ao sexo.